2015
DOI: 10.1128/cvi.00690-14
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Immunogenicity of Single-Dose AdVAV Intranasal Anthrax Vaccine Compared to Anthrax Vaccine Absorbed in an Aerosolized Spore Rabbit Challenge Model

Abstract: cAdVAV is a replication-deficient adenovirus type 5-vectored vaccine expressing the 83-kDa protective antigen (PA83) from Bacillus anthracis that is being developed for the prevention of disease caused by inhalation of aerosolized B. anthracis spores. A noninferiority study comparing the efficacy of AdVAV to the currently licensed Anthrax Vaccine Absorbed (AVA; BioThrax) was performed in New Zealand White rabbits using postchallenge survival as the study endpoint (20% noninferiority margin for survival). Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 30 publications
1
6
0
2
Order By: Relevance
“…The data showed that both the F1mutV-PA and PA vaccines induced high levels of anti-PA antibodies as well as LeTx-neutralizing antibodies at day 20 (Figures 8 C,D). These titers are similar to that reported for the licensed AVA ( 50 , 51 ).…”
Section: Resultssupporting
confidence: 87%
“…The data showed that both the F1mutV-PA and PA vaccines induced high levels of anti-PA antibodies as well as LeTx-neutralizing antibodies at day 20 (Figures 8 C,D). These titers are similar to that reported for the licensed AVA ( 50 , 51 ).…”
Section: Resultssupporting
confidence: 87%
“…In a SARS-CoV-2 challenge model in rhesus macaques, a single intramuscular administration of an adenovectored vaccine candidate was shown to significantly reduce viral load in the bronchoalveolar lavage fluid and lower respiratory tract tissue but the level of viral replication in the nasal cavity was unaffected [ 46 ]. Conversely, nasal administration of replication-deficient human Ad5-vectored vaccines, such as AdCOVID, mimic natural infection of respiratory viruses and stimulate strong protective immunity, both systemically and mucosally, while maintaining an established clinical safety profile [ 47 , 48 , 49 , 50 , 51 ]. Intranasal vaccination stimulates mucosal IgA antibodies, providing a first line of defense at the point of respiratory pathogen inoculation [ 52 ], which correlates well with protection from respiratory infections such as influenza [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obiltoxaximab is another monoclonal antibody, which could also neutralize the free PA of B. anthracis and inhibits the lethal effects of anthrax toxins (65). These agents have proven effective in eliminating the inhalational anthrax infection after one treatment intervention conducted on rabbits and monkeys (66).…”
Section: Potential Anti-virulence Therapeutics As Effective Treatmentsmentioning
confidence: 99%